2013
DOI: 10.1002/anie.201302929
|View full text |Cite
|
Sign up to set email alerts
|

An Anion‐Modulated Three‐Way Supramolecular Switch that Selectively Binds Dihydrogen Phosphate, H2PO4

Abstract: An anionic three-way switch A bipyridyl bisurea-based anion receptor that is highly selective for dihydrogen phosphate demonstrates spectroscopically distinct anion bound conformations toward halides and select oxoanions. 1H NMR studies show the differing anion induced conformations are reversible allowing this system to function as a three-way molecular switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…Known bis-aniline 16 was similarly prepared from 6,6′-dibromo-2,2′-bipyridine. 34 Independent treatment of 15 and 16 with p -toluenesulfonyl chloride in pyridine provided expanded receptors 11 and 12 in moderate to very good yield.…”
Section: Resultsmentioning
confidence: 99%
“…Known bis-aniline 16 was similarly prepared from 6,6′-dibromo-2,2′-bipyridine. 34 Independent treatment of 15 and 16 with p -toluenesulfonyl chloride in pyridine provided expanded receptors 11 and 12 in moderate to very good yield.…”
Section: Resultsmentioning
confidence: 99%
“…Chloride must sit inside the cleft formed from an S or W arrangement in order to H-bond to the R 3 N + H and HC Py protons, similar to what is observed when our related bipyridine-based receptor binds chloride or bromide (referred to as the Z arrangement). 30 As discussed, additional equilibria arise during the titration of bromide or chloride into 1 + , likely indicating a competing 1: 2 interaction. What is unclear is whether this secondary equilibrium occurs with the pyridinium NH proton ( 1:2 S ) or CH proton ( 1:2 W ).…”
Section: Resultsmentioning
confidence: 93%
“…Within our group we have found that an aryl–ethynyl scaffold can adopt varying conformations in the solid state or in solution when influenced by a guest (see below). [2729] These conformational changes have a direct effect on the conjugation throughout the system, giving rise to differences in the emission spectra.…”
Section: Sensing Strategiesmentioning
confidence: 99%
“…We have previously described a series of both bis(-sulfonamido)- and bis(urea)ethynylpyridines that exhibit positive fluorescent responses to anions with the right combination of electron-donating and/or electron-withdrawing substituents on the pendant phenyl rings. [4, 2529, 77] The bis-ureas (e.g., 25 – 28 , Figure 17) exhibit a rich solvent-based conformational dependence, showing in the solid state that “S”-, “U”- and “W”-type conformations are all possible depending on solvent guests (for instance, “S” shown in 28 , “U” shown in 25 – 27 ). [27] …”
Section: Charged Speciesmentioning
confidence: 99%
See 1 more Smart Citation